The Increasing Of Dental And Mouth Health Through The Practice Of A Toothbrush Children’s School - Matilda Bupu Ria; Brigita Dina Manek; Deviser lina Babys; Maria Magdalena Theofila Duka (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Tooth decay in children become one of the biggest health problems in children. Factors that influence this disease were knowledge, and behavior factors. In terms of increasing knowledge of children's health, especially dental and oral health, counseling has a target to be able to change individual behavior for the better. While the practiced of brushing teeth was an action that needs have been taught to children so that it canbecome a good and healthy habit.Dental health counseling, and tooth brushing practices were considered effective during the new normal period as it was today. The midwifery extension team from Stikes maranatha kupang prevented tooth decay in children through health promotion activities carried out on 36 children of GMIT Pukdale Elementary School. It was hoped that these activities could been an effort to reduce the prevalence of dental caries in indonesia, especially in the kupang region of south east of nusaeasteren